SAT0456 Heat Shock Protein 90 Plasma Levels Correlate with Disease Activity, Lung Involvement and Skin Fibrosis in Systemic Sclerosis. (9th June 2015) - Storkanova, H.; Hulejova, H.; Spiritovic, M.; Prajzlerova, K.; Becvar, R.; Pavelka, K.; Vencovsky, J.; Distler, J.H.; Senolt, L.; Tomcik, M.
Abstract : Background: Our previous study demonstrated that Heat shock protein 90 (Hsp90) is overexpressed in the skin of patients with systemic sclerosis (SSc), in cultured SSc fibroblasts and preclinical models of SSc in a TGF-β dependent manner. We showed that Hsp90 is a new regulator of canonical TGF-β signalling and its inhibition prevents stimulatory effects of TGF-β on collagen synthesis, and prevents dermal fibrosis in three different preclinical models of SSc [1]. Objectives: To assess Hsp90 in circulation of SSc patients and characterize its potential association with skin changes and SSc-related features. Methods: A total of 40 patients (36 females; mean age 53.9; disease duration 5.0 years; dcSSc/lcSSc =9/31) who met the EULAR/ACR 2013 criteria for SSc and 39 healthy individuals matched by age and sex were included in this study. Plasma Hsp90 levels were measured by ELISA (eBioscience, Vienna, Austria). ANA, ENA complex, ESR and CRP were evaluated. SSc-related manifestations were obtained from the Czech Registry of SSc patients. Interstitial lung disease, pulmonary arterial hypertension, oesophageal dysmotility, cardiac and renal involvement, nailfold capillaroscopy and Raynaud's phenomenon were recorded. Skin changes were assessed using the modified Rodnan skin score and EUSTAR SSc activity score was determined. Data are presented as median (IQR). Results: Hsp90 plasma levels were comparable between SSc patients and healthy controls (10.8 (9.2-15.5) vs. 10.1 (8.2-12.8) ng/ml, p=0.250) and between patients with diffuse cutaneous (dc)SSc and limited cutaneous (lc)SSc (11.6 (9.3-15.8) vs. 10.4 (8.6-15.6) ng/ml, p=0.710). Of particular interest, the levels of Hsp90 positively correlated with EUSTAR SSc activity score (r =0.418, p=0.007). Furthermore, Hsp90 plasma levels negatively correlated with forced vital capacity (FVC), forced expiratory volume in 1s (FEV1) and diffusing capacity for carbon monoxide (DLCO) (r = - 0.457, p=0.004; r = - 0.346, p=0.033; r = - 0.444, p=0.005, respectively). In addition, only in patients with dcSSc, Hsp90 levels positively correlated with the modified Rodnan skin score (r =0.742, p=0.022). Using Bonferroni's correction (p<0.01), relations between Hsp90 and EUSTAR SSc activity score, FVC and DLCO were approved. The presence of autoantibodies (ANA, anti-centromere, anti-Scl70), a pathological capillaroscopic pattern (early, active, late), and the individual clinical symptoms of SSc did not significantly affect Hsp90 plasma levels. Conclusions: We demonstrate that plasma levels of Hsp90, in contrast to local upregulation in fibrotic skin, are comparable between SSc patients and healthy controls. However, increased plasma levels of HSP90 in SSc patients are associated with higher disease activity, deteriorated parameters of lung involvement, and, particularly in dcSSc patients, with skin involvement. These data further highlight the role of Hsp90 as a regulator of fibroblast activation and tissue fibrosis in SSc. References: Tomcik M et al. Heat shock protein 90 (Hsp90) inhibition targets canonical TGF-β signalling to prevent fibrosis. Ann Rheum Dis.2014;73(6):1215-22. Acknowledgements: Supported by MHCR023728. Disclosure of Interest: None declared